Field Book: Pennsylvanian Plant Fossils of Illinois - Collinson, Charles William, 1923-2011; Skartvedt, Romayne, 1916-1990; Litterer, Marie E. (Marie Ellen), 1925-2002 (Salt Lake City, UT : Project Gutenberg, 2021)
"Field Book: Pennsylvanian Plant Fossils of Illinois" by Charles Collinson and Romayne Skartvedt is a scientific publication written in the mid-20th century. This book serves as a guide for beginners interested in collecting and classifying plant fossils found in Illinois, particularly focusing on those from the Pennsylvanian epoch, which is known for its rich fossil deposits. The book provides detailed illustrations and descriptions of a wide variety of plant fossils that thrived during the Pennsylvanian period, contributing to the formation of notable coal beds in the region. It explains the geological and environmental conditions that allowed for the remarkable preservation of these plants, including areas like Mazon Creek where fossils can be collected. The authors also guide readers on collecting techniques, identifying different fossil types$1 (Bsuch as molds, casts, petrifactions, and compressions$1 (Band discuss the significance of these fossils in understanding ancient ecosystems. Overall, this field book is a valuable resource for amateur collectors and those interested in paleobotany, offering insights into the ancient flora of Illinois and guidance for effective fossil hunting. (This is an automatically generated summary.)s
Release date is 2021-07-06
Stephen Hutcheson and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Paleobotany -- Illinois; Paleobotany -- Pennsylvanian